Re-thinking cell cycle regulators: the cross-talk with metabolism - Fajas, Lluis (Frontiers in Oncology, 2013)
Analysis of genetically engineered mice deficient in cell cycle regulators, including E2F1, cdk4, and pRB, showed that the major phenotypes are metabolic perturbations. These key cell cycle regulators contribute to lipid synthesis, glucose production, insulin secretion, and glycolytic metabolism. It has been shown that deregulation of these pathways can lead to metabolic perturbations and related metabolic diseases, such as obesity and type II diabetes. The cyclin–cdk–Rb–E2F1 pathway regulates adipogenesis in addition to its well-described roles in cell cycle regulation and cancer. It was also shown that E2F1 directly participates in the regulation of pancreatic growth and function. Similarly, cyclin D3, cdk4, and cdk9 are also adipogenic factors with strong effects on whole organism metabolism. These examples support the emerging notion that cell cycle regulatory proteins also modulate metabolic processes. These cell cycle regulators are activated by insulin and glucose, even in non-proliferating cells. Most importantly, these cell cycle regulators trigger the adaptive metabolic switch that normal and cancer cells require in order to proliferate. These changes include increased lipid synthesis, decreased oxidative metabolism, and increased glycolytic metabolism. In summary, these factors are essential regulators of anabolic biosynthetic processes, blocking at the same time oxidative and catabolic pathways, which is reminiscent of cancer cell metabolism.